Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.37766/inplasy2021.12.0086
|View full text |Cite
|
Sign up to set email alerts
|

A Bayesian Network Meta-analysis of the Effect of Acute Exercise on Executive Function in Middle-aged and Senior People

Abstract: Review question / Objective: Objective: To compare the intervention effect of multiple acute movement formulas on the executive function in middle-aged and senior people and to provide references for the discussion of the plans for precise movements. P: middle-aged and senior people elderly people; I: acute exercise; C: reading or sitting; O: Executive Function; S: RCT/crossover. Information sources: Randomized searches were carried out in Chinese databases such as CNKI, Wanfang Database, VTTMS, SinoMed and fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…[48] In terms of single session duration, the duration of 40 min exercise was more effective. Some studies have shown that exercise duration may be an important moderator of the intervention effects of exercise on executive function [49] The effects of prolonged exercise on cognitive bene ts are largely negligible and may even be detrimental if the duration is too long or too short. These ideas are further supported by the self-control theory.…”
Section: Discussionmentioning
confidence: 99%
“…[48] In terms of single session duration, the duration of 40 min exercise was more effective. Some studies have shown that exercise duration may be an important moderator of the intervention effects of exercise on executive function [49] The effects of prolonged exercise on cognitive bene ts are largely negligible and may even be detrimental if the duration is too long or too short. These ideas are further supported by the self-control theory.…”
Section: Discussionmentioning
confidence: 99%